School Discipline Policies, Perceptions of Justice, and In-School Delinquency. (September 2019) - Fissel, Erica R.; Wilcox, Pamela; Tillyer, Marie Skubak
School crime has been a national issue for nearly 40 years and remains a concern for students, administrators, parents, and the public. Schools engage in numerous strategies aimed at curbing crime, ranging from harsh disciplinary practices to proactive strategies focused on gaining student compliance. This study examines the impact of disciplinary practices on in-school delinquency, while also considering the influence of students' perceptions of injustice. Using student- and school-level data from the Rural Substance Abuse and Violence Project and hierarchical Poisson regression analyses, findings reveal that students' perceptions of injustice were significantly related to in-school delinquency, while proactive and reactive discipline practices, spanning the punitiveness continuum, were not. The findings provide tentative guidance for school-based discipline management policies and practices.